Emergence and development of Dianthus chinensis and Limonium sinuatum seedlings on commercial substrate (Research, Society and Development, 2021)
Limonium sinuatum and Dianthus chinensis are plant species of great importance in Brazilian floriculture, being propagated by seed, therefore, the characteristics of the substrates used are respectable in seedlings emergence and development process. Thus, the objective of this research was to evaluate the influence of two commercial substrates on emergence and development of Limonium sinuatum and Dianthus chinensis seedlings. The experiment was conducted in a greenhouse (Pad & Fan type) at São Paulo State University. The treatments were: T1 – Basaplant® and T2 – Tropstrato®, for both species, whose seeds were germinated in expanded polystyrene trays of 128 cells, being eight replicates, containing 8 seeds/replicate. The evaluated traits were: percentage of emergence, emergence speed index, mean emergence time, shoot height, root length and seedlings fresh and dry mass. The substrate characteristics evaluated were: pH, electrical conductivity, macroporosity, microporosity, total porosity, density and water retention capacity. The experimental design was completely randomized, and data were submitted to analysis of variance to Tukey test at 5% to compare the means. The emergence of Limonium sinuatum and Dianthus chinensis were impaired, possibly due to low electrical conductivity provided by substrates. However, Basaplant® substrate favoured the development of evaluated species in relation to aerial part length, root length and total fresh and dry mass, which is recommended for using as substrate for both species.